La politisation des glaciers en Argentine : une analyse de l’application de la loi nationale sur les glaciers (2010) - Lorena Bottaro; Marian Sola Álvarez (Cahiers des Amériques Latines)
In this article we explore the birth of « self-mobilizing » community associations and the articulation and mobilization process of different stakeholders whose efforts led to the enactment of the Law on Minimum Standards for the Protection of Glacial and Periglacial Environment. By sanctioning rules which lay a common ground of environmental protection at the national level, the Argentinian National Congress produced a powerful legal instrument for activists, including those who used it to mobilize against the growth of megamining.We are interested in identifying how the politicization of glaciers is constructed on a dual scale: one national, one provincial. At the national level, we focus on the process that framed the debate and actions leading to the enactment of the law. In this context, we will investigate how the issue was treated in the legislative sphere and what the role of the national executive was. At the provincial level, we will explore the strategies and institutional structures designed to hinder the implementation of the law by provincial governments that promote the expansion of megamining in their territories.